(untitled) (Comparatismi, 2023)
Anger is the emotion that undermined the bipolar models of analysis (Carver, White, 1994), based on valence as a distinction for the differentiation between homogeneous groups of basic emotions, favoring models with discrete emotions or their fusion (Nabi, 1999; 2010. Dillard, Peck, 2001). Anger, despite being a negative emotion, which should therefore activate “the behavioral inhibition system” (BIS), instead generates an active reaction, that is, it stimulates the “behavioral approach system” (BAS). This already appeared clear in the pioneering study conducted by Greimas on anger (Greimas, [1983] 1987), placed within the work dedicated to the modalizations of the subject. From the modal point of view, in fact, anger can be defined as the coexistence of the modalization of wanting-to-do and not-being-able-to-do which generates a state of frustration, in turn followed by active behavior. The process that provides for (i) realistic narration of social degradation, (ii) stimulation of the state of frustration in the reader, (iii) activation of behaviors and practices of social reaction to the state of degradation, therefore, is the basis of all those cultural policies which are based on the dissemination of social-themed narratives with the aim of raising public awareness. This narrative should favor, together with the process of empathic identification, the understanding of phenomena of social degradation, and the formulation of moral judgments in line with the perspective of an active reaction to such phenomena as a collective problem. This paper presents a case study conducted on Roberto Saviano’s book Gomorra, which inaugurated the narrative current of the “New Italian Realism” and which is historically connected to a tradition of realism that originated in the post-war period. Saviano’s nonfiction novel, which has favored a reaction to phenomena of social degradation connected to organized crime, is an interesting persuasive model for the study of narrative strategies that support the involvement of public opinion. This paper also presents the results of an experimental study of an exploratory nature, aimed to research basic knowledge on narrative strategies for the stimulation of anger as a factor in raising awareness of public opinion. The experiment is conducted in within mode on a small group of university students, randomly selected based on their willingness to participate. The experimental setting is a biometrics laboratory made up of Tobii Spectrum 300 desk stations, where the subjects read in desk mode, using the Tobii Pro Lab software, the story from the book Gomorra called Hollywood, and watch the film version of the same story made by Matteo Garrone. During reading and video reading, eye tracking data is collected and facial reaction is processed with the Noldus Face Reader software. At the end of the reading, a Narrative Transportation Scale (Green, Brock, 2000; 2002) is administered which evaluates identification and emotional involvement of the reader, and a focus group is created on the emotional reaction by analyzing the parameters (phenomenological, physiological, expressions, behaviors and emotional motivations) of Roseman’s model (2001). The aim of the study is to identify which narrative and discursive structures are more closely connected to the activation of the emotional state of anger, and if there are substantial differences between the verbal and visual code in the activation of anger, starting from the same basic narrative structure and thematic content.